Innovative public–private partnership to target subsidised antimalarials: a study protocol for a cluster randomised controlled trial to evaluate a community intervention in Western Kenya. Issue 3 (20th March 2017) - Laktabai, Jeremiah; Lesser, Adriane; Platt, Alyssa; Maffioli, Elisa; Mohanan, Manoj; Menya, Diana; Prudhomme O'Meara, Wendy; Turner, Elizabeth L
Abstract : Introduction: There are concerns of inappropriate use of subsidised antimalarials due to the large number of fevers treated in the informal sector with minimal access to diagnostic testing. Targeting antimalarial subsidies to confirmed malaria cases can lead to appropriate, effective therapy. There is evidence that community health volunteers (CHVs) can be trained to safely and correctly use rapid diagnostic tests (RDTs). This study seeks to evaluate the public health impact of targeted antimalarial subsidies delivered through a partnership between CHVs and the private retail sector. Methods and analysis: We are conducting a stratified cluster-randomised controlled trial in Western Kenya where 32 community units were randomly assigned to the intervention or control (usual care) arm. In the intervention arm, CHVs offer free RDT testing to febrile individuals and, conditional on a positive test result, a voucher to purchase a WHO-qualified artemisinin combination therapy (ACT) at a reduced fixed price in the retail sector. Study outcomes in individuals with a febrile illness in the previous 4 weeks will be ascertained through population-based cross-sectional household surveys at four time points: baseline, 6, 12 and 18 months postbaseline. The primary outcome is the proportion of fevers that receives a malaria test from any source (CHV or health facility). The main secondary outcome is the proportion of ACTs used by people with a malaria-positive test. Other secondary outcomes include: the proportion of ACTs used by people without a test and adherence to test results. Ethics and dissemination: The protocol has been approved by the National Institutes of Health, the Moi University School of Medicine Institutional Research and Ethics Committee and the Duke University Medical Center Institutional Review Board. Findings will be reported on clinicalstrials.gov, in peer-reviewed publications and through stakeholder meetings including those with the Kenyan Ministry of Health. Trial registration number: Pre-results, NCT02461628 .